APLIKASI METODE RESISTIVITAS DC UNTUK PENDUGAAN BIDANG LONGSOR DAN BIDANG GELINCIR DI JALAN KERETA API KM 107 (1/5), CIGANEA, PURWAKARTA, JAWA BARAT - Hilman Suwargana (JURNAL GEOMINERBA (JURNAL GEOLOGI, MINERAL DAN BATUBARA), 2018)
Landslide which occurred at the railroad km 107 (1/5) Ciganea, Purwakarta, West Java, is tirggered by rainwater seeping into the porous rock such as breccias, sandstones, and soil, so as increasing the weight of the rock/soil. When the water is up to the rock that is impermeable, then the water will be moving over the rock, so that the rock serves as a sliding plane. If there is a rock that is above the sliding plane, then the rock will move in the sliding plane. One of the geophysical methods that can detect areas of landslide and sliding plane is Resistivity method. Resistivity method can detect areas of landslide and sliding plane based on value of rock resistivity. Data acquisition using method of electrical resistivity tomography. Based on resistivity section of line 1 which has been correlated with the drill data of BM-05, obtained litology at sliding plane is sandy clay with resistivity values of: (3.37 - 5.12) Ohm.m and claystone with resistivity values of < 3,36Ohm.m, whereas litology of landslide plane is sandstone with resistivity of: (7.81 - 18.00) Ohm.m and breccias with resistivity >18.1 Ohm.m.